Measurement of Arctic sea ice from satellite altimetry: the potential and limitations of CryoSat-2 SARIn mode - Di Bella, Alessandro (Technical University of Denmark, 2019)
Sea ice plays a fundamental role in the global climate system, influencing directly the albedo of our planet and regulating the exchange of heat between the atmosphere and the ocean. Observations from satellites and submarine data have shown a rapid reduction of the ice-covered area and a general thinning of Arctic sea ice in the last three decades. Satellite altimetry can be used to infer sea ice thickness from the direct measurement of the sea ice freeboard, i.e. the height of the ice surface above the local sea level. However, in the freeboard-to-thickness conversion the freeboard and the associated errors are typically multiplied by a factor of ∼10, thus, it is fundamental to both improve the accuracy of freeboard estimates as well as to minimise their uncertainty. The largest source of freeboard uncertainty, after the contribution due to the lack of knowledge of the Arctic snow cover, originates from the poor knowledge of the sea surface height (SSH) in icecovered regions. CryoSat-2’s (CS) interferometric mode (SARIn) enables to process waveforms whose power echo is dominated by the strong reflection from off-nadir leads, referred to as "snagged" waveforms, which are usually discarded in common SAR altimetry data processing. In fact, the available phase information can be used to correct for the associated range error and to retrieve a larger number of valid SSH measurements which, ultimately, increases the accuracy as well as reduces the uncertainty of the area-averaged SSH. The SARIn phase information is currently not used by the scientific community in the estimation of sea ice freeboard and thickness, probably because of the scarce SARIn coverage of the Arctic Ocean. However, despite changes in the SARIn acquisition mask throughout the years, CS still operates in SARIn mode along the entire coastline of the Arctic Ocean. In this work, an assessment of the potential and limitations of the CS SARIn mode with respect to the estimation of the sea ice freeboard and thickness in the Arctic is performed. ...